Degradation of mouse locomotor pattern in the absence of proprioceptive sensory feedback - Akay, Turgay (Proc Natl Acad Sci U S A, 2014)
Mammalian locomotor programs are thought to be directed by the actions of spinal interneuron circuits collectively referred to as “central pattern generators.” The contribution of proprioceptive sensory feedback to the coordination of locomotor activity remains less clear. We have analyzed changes in mouse locomotor pattern under conditions in which proprioceptive feedback is attenuated genetically and biomechanically. We find that locomotor pattern degrades upon elimination of proprioceptive feedback from muscle spindles and Golgi tendon organs. The degradation of locomotor pattern is manifest as the loss of interjoint coordination and alternation of flexor and extensor muscles. Group Ia/II sensory feedback from muscle spindles has a predominant influence in patterning the activity of flexor muscles, whereas the redundant activities of group Ia/II and group Ib afferents appear to determine the pattern of extensor muscle firing. These findings establish a role for proprioceptive feedback in the control of fundamental aspects of mammalian locomotor behavior.